Mid-urethral sling with proper sling tension is an effective treatment for stress urinary incontinence in women after pelvic radiotherapy: a pilot study of case series - Guan, Xing; Wang, Fei; Zhang, Di; Qiao, Peng; Qin, Yan; Wang, Biao (Frontiers in Surgery, 2025)
BackgroundAt present, consensus on the management of female stress urinary incontinence (SUI) after pelvic radiotherapy is lacking. We aim to assess the clinical effects of mid-urethral sling (MUS) for the treatment of SUI after pelvic radiotherapy in women.MethodsWe conducted a retrospective review of the clinical database of female with SUI after pelvic radiotherapy from June 2015 to February 2022. The clinical efficacy was evaluated by International Consultation on Incontinence Questionnaire-Short Form (ICI-Q-SF) questionnaire, maximum flow rate (Qmax) and postvoid residual (PVR) urine. All patients were reviewed postoperatively in an outpatient clinic.ResultsWe identified 26 patients with mean age of 59.35 ± 7.32 years. All the patients who suffered from SUI had a history of gynaecological malignancies and received pelvic radiotherapy. 21 patients (80.77%, 95% CI: 0.621–0.915) were considered to have successfully improved after surgery, the ICI-Q-SF scores were lower than the pre-operative at 2 weeks, 6 months and 1 year postoperatively (P < 0.01). After 1-year follow-up, none of the patients had mesh erosion.ConclusionSUI following radiotherapy for the treatment of pelvic malignancy can be challenging to manage. MUS is a highly effective and safe option for the treatment of SUI after radiotherapy, additionally, that proper sling tension is the key to the success of the procedure.